2006
DOI: 10.1063/1.2204634
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of swirling flow in a cylinder with rotating top and bottom

Abstract: A numerical investigation of oscillatory instability is presented for axisymmetric swirling flow in a closed cylinder with rotating top and bottom. The critical Reynolds number and frequency of the oscillations are evaluated as function of the ratio of angular velocities of the bottom and the top ͑ = ⍀ bottom / ⍀ top ͒. Earlier linear stability analysis ͑LSA͒ using the Galerkin spectral method by Gelfgat et al. ͓Phys. Fluids, 8, 2614 ͑1996͔͒ revealed that the curve of the critical Reynolds number behaves like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…At the inception of any instability breaking the axisymmetry of the flow, a three-dimensional solution of the Navier-Stokes equations is required, thereby increasing considerably the complexity of the task. The last remark justifies the observed changes in terms of numerical modeling of Lopez' group and Sørensen's group, to allow them to investigate axisymmetry breaking in the closed cylinder case [5,6,[41][42][43]. Therefore, three-dimensional flow structures have started being simulated more recently, see Gelfgat et al [44], Sotiropoulos & Ventikos [11], Sotiropoulos et al [45], Marques & Lopez [46], Blackburn & Lopez [5,6], Serre & Bontoux [47], Blackburn [48], and Lopez [49].…”
Section: The Lid-driven Cylindrical Cavity Flowmentioning
confidence: 86%
“…At the inception of any instability breaking the axisymmetry of the flow, a three-dimensional solution of the Navier-Stokes equations is required, thereby increasing considerably the complexity of the task. The last remark justifies the observed changes in terms of numerical modeling of Lopez' group and Sørensen's group, to allow them to investigate axisymmetry breaking in the closed cylinder case [5,6,[41][42][43]. Therefore, three-dimensional flow structures have started being simulated more recently, see Gelfgat et al [44], Sotiropoulos & Ventikos [11], Sotiropoulos et al [45], Marques & Lopez [46], Blackburn & Lopez [5,6], Serre & Bontoux [47], Blackburn [48], and Lopez [49].…”
Section: The Lid-driven Cylindrical Cavity Flowmentioning
confidence: 86%
“…Here we will analyze a particular configuration, the von Kármán swirling flow, where two different propellers are rotating inside a cylindrical cavity. These flows have been studied analytically [3,4], numerically [5,6,7] and experimentally [8,9,10]. Recently it has been shown that they can present multistability and memory effects [11].…”
mentioning
confidence: 99%
“…These flows have been studied analytically [3,4], numerically [5,6,7] and experimentally [8,9,10]. Recently it has been shown that they can present multistability and memory effects [11].…”
mentioning
confidence: 99%
“…Two counter-rotating propellers are used to develop turbulence in a cylindrical cavity filled with water. This model system has been largely studied numerically [3][4][5], theoretically [6,7] and experimentally [8][9][10][11]. This kind of flow is particularly used in magnetohydrodynamics (MHD) experiments.…”
Section: Introductionmentioning
confidence: 99%